(untitled) (Wymondham, 2001)
Internationally acclaimed authors from diverse fields present comprehensive reviews of all aspects of Industrial and Environmental Biotechnology. Based on presentations given at the key International symposium on Biotechnology in Karachi in 1998, the articles have been extensively revised and updated
Keywords: Biotechnology,Agricultural biotechnology,Công nghệ sinh học; Congresses